Evidential Strategies in Latin - Zheltova, Elena (Hyperboreus, 2018)
The paper aims at drawing attention to certain phenomena in Latin which can be treated as evidential strategies. In Introduction, a brief overview of the existing viewpoints concerning the grammatical category of evidentiality is provided, then a question of the interrelation between evidentiality and epistemic modality is touched upon and author’s methodological approach to the issue is outlined. In the main part of the paper, the author provides an overview of the linguistic strategies used to mark the main types of access to information, i.e. direct (perceptual) evidence, indirect inferential (or presumptive) evidence, and indirect reported evidence. The author singles out thirteen morphological and syntactic means to express different kinds of evidential values (e.g. Inﬁnitive or Participle constructions, historic present, modal use of the subjunctive mood with inferential or reportative overtones, logophoric use of the reﬂexive pronouns etc.). The author’s claim is that these strategies belong to the grammar rather than to the lexicon of the Latin language and, therefore, can be treated as evidential strategies. Considering these grammatical phenomena as evidential strategies may enrich one’s understanding of the Latin language and help to realize that the traditional inventory of grammatical forms and constructions can express many more values than one might have expected.